1168. Higher Glycosylated Hemoglobin (A1c) Levels are Associated with Increased Mortality from Cryptococcus Infection. (31st December 2020) - Archuleta, Solana; Sillau, Stefan; Franco-Paredes, Carlos; Henao-Martinez, Andres
Abstract: Background: Diabetes mellitus is a well-established risk factor for the development of bacterial infections. However, the role of diabetes mellitus as a risk factor in the occurrence of Cryptococcosis is unknown. The aim of the study was to determine whether diabetes and A1c levels were independent risk factors for infection and mortality in Cryptococcus infection. Methods: A retrospective hospital-based case-control study matched by age and gender (96 cases and 125 controls) was performed in patients tested for Cryptococcus infection at University of Colorado Hospital from 2001-2019 (n=221). Data was extracted through RedCap. A multivariable logistic regression model was used to identify predictors of infection and mortality. Results: Diabetes mellitus was present in 24 cases (25.0%) and 24 controls (19.2%). In cases, the mean age was 54 years, 79% were men, and diabetes was the only known risk factor in 6 cases (6.3%) and accompanied additional risk factor in 18 cases (18.8%). Other common risk factors included: HIV (39.9%), steroid use (24.7%), malignancy (23.2%), solid organ transplant recipients (18.1%), and cirrhosis (5.2%). Cryptococcal meningitis (49.0%) followed by pulmonary infection (36.5%) were the most common sites of infection. The mean A1c value for cases vs. controls was 6.5 ± 1.5 vs. 6.2 ± 1.8 mmol/L, p=0.43. Overall mortality was 27.3% vs. 26.9% among cases and controls, respectively. Among cases, the risk of death was higher for patients with diabetes, although not significantly (39.1% vs 23.1%, p= 0.137). Adjusted for gender, age and case/control; for every 1-point increase in A1c levels, the odds of mortality increased by 40% (OR = 1.4, CI: 1.0-1.9, p= 0.045). Conclusion: Diabetes mellitus alone is an uncommon risk factor for acquiring Cryptococcus infection. However, uncontrolled diabetes in Cryptococcosis may worsen outcomes from infection, including increased mortality. Glucose control interventions may improve clinical outcomes in patients with cryptococcal infection. Disclosures: All Authors : No reported disclosures